Analysis of Factors Affecting the Open Unemployment Rate Unemployment Rate in Indonesia in 2018-2022 - Mahdy, Salim Imam; Manan, Afni Abdul; Shifa, Mutiara (UNIVERSITAS SERAMBI MEKKAH, 2025)
The purpose of this study is to determine the unemployment rate in Indonesia. If unemployment does not improve people's welfare based on per capita income. This study uses the years 2018 to 2022. This study uses panel data analysis. The value of the technical variable is 4.893448, the standard deviation value is 1.080620. Panel data regression is carried out. We test this survey data with data using panel data of dependent variables which include dependent variables, open unemployment rates, and independent variables.